Comprehensive Impact of Multiplanar Malalignment on Prosthetic Mechanics Under Gait Loading After Total Knee Arthroplasty—A Finite Element Analysis - Yichao Luan; Min Zhang; Xiang Dong; Hongping Duan; Zhiwei Wang; Zhichang Li; Cheng‐Kung Cheng (Orthopaedic Surgery, 2025)
ABSTRACT Background Component alignment is a key factor influencing clinical outcomes after total knee arthroplasty (TKA). Previous studies have shown that single‐plane alignment can significantly affect knee joint kinematics and biomechanics. However, the comprehensive impact of multiplanar malalignment has been rarely investigated. Objective This study aimed to investigate the influence of the multiplanar malalignment combination on the polyethylene tibial liners under gait loading, a primary activity of daily life, as well as the degree of the influence of the alignments on the different planes. Method A validated finite element model of a cruciate‐retaining knee prosthesis under gait loading was used in this study. Five alignment parameters (−5°, −3°, 0°, 3°, 5°) on each plane (coronal, sagittal, and transverse) were selected to simulate clinical alignment errors, resulting in 125 models combining various alignment errors across the three planes. Boundary and loading conditions were set according to ISO 14243‐3:2014. The maximum von Mises stress and contact stress during a gait cycle were recorded for statistical analysis. A polynomial model was used for regression analysis, with the degree of influence of each alignment error on von Mises and contact stress determined by examining the quadratic coefficients. Results The highest Mises and contact stress values occurred with alignment errors of 5° varus, 5° flexion, and 5° internal rotation on the coronal, sagittal, and transverse planes, respectively. The lowest stress values were observed with a combination of 3° valgus, 5° flexion, and 0° internal rotation. The regression analysis yielded an R 2 value of 0.69 between alignment errors and Mises stress, with quadratic coefficients of 0.096, 0.013, and 0.064 for the coronal, sagittal, and transverse alignments, respectively. For contact stress, the R 2 was 0.697, with quadratic coefficients of 0.083, 0.002, and 0.026 for the coronal, sagittal, and transverse alignments, respectively. Conclusion The coronal alignment of the lower limb has the most significant impact on both Mises stress and contact stress of the tibial liner, followed by the rotational alignment of the tibial component. In contrast, the sagittal alignment of the femoral component has the least influence.